Improvement of Small Scale Cocoa Fermentation Using Lactobacillus fermentumas Starter Culture - Misnawi Misnawi; Ariza Budi Tunjungsari; Noor Ariefandie Febrianto; Resa Setia Adiandri; Fahrizal Fahrizal; Fahrurrozi Fahrurrozi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2017)
Low harvest amount of cocoa smallholder has became a great constraint for farmer in order to carry out a proper postharvest practice. Low production of raw cocoa beans cause farmers are not able to ferment their cocoa beans that lead to low quality of cocoa beans produced. Addition of starter culture to improve the fermentation performance has been previously reported by some researchers. In this study,  Lactobacillus fermentum(LF) inoculum was used as stater culture for small scale cocoa fermentation (15 kg). The LF culture (107 CFU/gr) was added in several concentration (1, 2.5, and 5% w/w) prior cocoa fermentation. The fermen-tation was carried out in 4 days (96 h) with once turning in 48 h. The result showed that the addition of LF in small batch of cocoa fermentation could improve the performance of fermentation and resulted in higher amount of fermented cocoa beans (70,34%, 5% LF) compared to natural fermentation and fair average quality (FAQ) beans (45% and 41%, respectively).  This research result is significantly important solving the issues of fermentation concerning with minimum quantity of cocoa needed. With this approach, small batch of cocoa fermentation even could result in comparable quality to full-batch fermentation.